Research on EMI suppression of high frequency isolate quasi-Z-source inverter based on chaotic frequency modulation. (November 2022) - Chen, Yan; Xing, Bin; He, Guodongxu; Jiang, Weihao; Wang, Zhenhan
Abstract: As a new type of topology inverter, the isolated quasi-Z-source inverter is suitable for photovoltaic power generation systems because of its high efficiency in power conversion, high boost ratio and electrical isolation. By increasing the operating frequency of the inverter, the inductance and capacitance volume of the inverter can be reduced, so that the inverter has higher power density. However, high-frequency switching actions will produce a large number of current and voltage sudden changes, leading to electromagnetic interference (EMI), affecting other components or the entire system and the stable operation of the power grid. Chaotic frequency modulation is a method to reduce the electromagnetic interference level of switching converters from the source. This method using the 10-scroll chaotic signal of the even-symmetric segmented Chen system as a spread spectrum signal to broaden the electromagnetic interference noise energy spikes to the surrounding continuous frequency bands, thereby reducing the spectrum peaks and making the system has better electromagnetic compatibility performance. In this paper, the high frequency isolated quasi Z-source photovoltaic grid-connected micro-inverter is studied, and the chaotic frequency modulation technology is used to suppress the electromagnetic interference of the inverter.